Evaluation of the Effects of Atorvastatin and N-Acetyl Cysteine on Platelet Counts in Patients with Primary Immune Thrombocytopenia: An Exploratory Clinical Trial - Lorena A Cervantes-Pérez; Gabino Cervantes-Guevara; Enrique Cervantes-Pérez; Guillermo Alonso Cervantes-Cardona; Adriana Nápoles-Echauri; Alejandro González-Ojeda; Clotilde Fuentes-Orozco; Gabino Cervantes-Pérez; Carlos A Reyes-Torres; Francisco Javier Hernández-Mora; Ana Lucia Ron-Magaña; Janet Cristina Vázquez-Beltrán; et al. (Medicina, 2023)
Objective: We aimed to evaluate the efficacy of the combination of atorvastatin and N-acetyl cysteine in increasing platelet counts in patients with immune thrombocytopenia who were resistant to steroid therapy or had a relapse after treatment. Material and Methods: The patients included in this study received oral treatment of atorvastatin at a dose of 40 mg daily and N-acetyl cysteine at a dose of 400 mg every 8 h. The desired treatment duration was 12 months, but we included patients who completed at least 1 month of treatment in the analysis. The platelet counts were measured prior to the administration of the study treatment and in the first, third, sixth, and twelfth months of treatment (if available). A p value < 0.05 was considered statistically significant. Results: We included 15 patients who met our inclusion criteria. For the total treatment duration, the global response was 60% (nine patients); eight patients (53.3%) had a complete response and one patient (6.7%) had a partial response. Six patients (40%) were considered as having undergone treatment failure. Of the responder group, five patients maintained a complete response after treatment (55.5%), three patients maintained a partial response (33.3%), and one patient (11.1%) lost their response to the treatment. All of the patients in the responder group had significant increases in their platelet counts after treatment (p < 0.05). Conclusion: This study provides evidence of a possible treatment option for patients with primary immune thrombocytopenia. However, further studies are needed.